Potential impact of ocular intense pulsed light on eyelash microbiome in severe meibomian gland dysfunction: report of 2 cases - Somboonna, Naraporn; Wongsaroj, Lampet; Watthanathirakawi, Attawut; Wanumkarng, Nattawut; Iam-a-non, Anchana; Pongpirul, Krit (Frontiers in Ophthalmology, 2023)
Meibomian gland dysfunction (MGD) is a prevalent worldwide eye disorder that causes eye irritation, inflammation, chronic dryness, and blurred vision. Traditional therapies offer temporary improvement, but their efficacy varies in severe MGD cases. Ocular intense pulsed light (IPL) has emerged as a novel therapy, providing long-term symptom relief and shorter treatment durations compared to traditional approaches. However, the impact of IPL on the bacterial community within the eyes remains limited. To address this, we conducted a preliminary study using metagenomics and next-generation sequencing. We compared the bacterial eyelash communities of Thai females with severe MGD before and after 2-4 IPL treatments, and against a group of healthy females. Our findings revealed higher bacterial diversity in healthy individuals compared to severe MGD cases. IPL treatments increased diversity in the MGD group, making their core bacterial community more similar to that of healthy subjects. Notably, the presence of Koribacteraceae in severe MGD and Bifidobacterium in healthy individuals and post-IPL-treated MGD exemplified this shift. Clustering analysis showed a closer relationship between post-IPLtreated MGH and healthy subjects, while the pre-IPL treatment group formed a separate branch.These results suggest that IPL treatment can reshape the eyelash microbiome in MGD cases, but further research is needed to understand the implications and the microbiome's role in MGD pathogenesis and treatment response.